Working With Interpreters as a Team in Health Care (WITH Care) Curriculum Tool Kit for Oral Health Professions - Anne Woll; Karin K. Quick; Cristiano Mazzei; Tehout Selameab; Jane L. Miller (Association of American Medical Colleges, 2020)
Introduction Limited English proficiency (LEP) patients face multiple care barriers and disproportionate risks for communication errors. Working with trained interpreters as a health care team can improve communication and drive high-quality care for LEP patients. Simulation and interprofessional education provide key strategies to address the critical training gap that exists at the intersection of patient safety, interprofessional practice, and cultural competence. Methods Using action research principles across 16 months, we created a 3.5-hour simulation-based training for oral health and interpreting learners. The curriculum included profession-specific orientations with didactic and experiential content, three immersive simulations using start-stop-rewind methodology, virtual scenarios, and summary reflection discussions. A comprehensive tool kit facilitated curriculum implementation and standardization. Results Forty-nine students from dentistry (first- through third-year predoctoral), dental hygiene, and dental therapy participated in this elective training during the 2017-2018 academic year; as required training, 126 third-year dental students participated in fall 2018. Students' familiarity with provider and interpreter best practices, appreciation of challenges faced by LEP patients, and confidence in skills working with spoken language interpreters increased. For all evaluation parameters, pre- and postsurvey ratings were statistically significant (chi-square tests, p < .001). Discussion The curriculum efficiently and effectively develops oral health and interpreting learners' abilities to work as a team with LEP patients. Curriculum design and resources address key barriers to feasibility and sustainability. The curriculum informs communication across all patient populations, revealing that getting by with partial understanding can be insufficient for any patient and any health care team.